Roles of vimentin in health and disease - Ridge Karen M; Eriksson John E; Pekny Milos; Goldman Robert D (COLD SPRING HARBOR LAB PRESS, PUBLICATIONS DEPT, 2022)
In this review, Ridge et al. discuss the essential functions of vimentin IFs revealed from studies of Vim(-/-) mice and cells derived from them.More than 27 yr ago, the vimentin knockout (Vim(-/-)) mouse was reported to develop and reproduce without an obvious phenotype, implying that this major cytoskeletal protein was nonessential. Subsequently, comprehensive and careful analyses have revealed numerous phenotypes in Vim(-/-) mice and their organs, tissues, and cells, frequently reflecting altered responses in the recovery of tissues following various insults or injuries. These findings have been supported by cell-based experiments demonstrating that vimentin intermediate filaments (IFs) play a critical role in regulating cell mechanics and are required to coordinate mechanosensing, transduction, signaling pathways, motility, and inflammatory responses. This review highlights the essential functions of vimentin IFs revealed from studies of Vim(-/-) mice and cells derived from them.